Impact of airports on spatial patterns of metropolitan employment: the case of Australia - Sonnenburg, Fabian; Braun, Boris (ERDKUNDE, 2017)
This paper aims to evaluate the localised effects of major airports on urban economies. We analyse employment change at privatised Australian airports, adjacent employment areas and major metropolitan employment centres. Time series employment data from 2001, 2006 and 2011 has been used to identify 61 employment centres in Sydney, Melbourne, Brisbane and Perth metropolitan areas. Regression models suggest that centre size, proximity to motorways and labour force accessibility are more important determinants of employment centre growth than airport accessibility. However, the privatisation of airports has also caused substantial development of commercial properties at airports, facilitating strong non-aviation-related employment growth at Brisbane and Perth airports. In contrast, Sydney and Melbourne airports have largely remained specialised centres with a strong focus on transport and warehousing. Due to significant increases in prices for land and real estate at privatised airports, spill-over effects can be identified around airports, transforming adjacent suburbs from industrial areas to more mixed use employment centres. The results of this study confirm research findings on employment growth around major US airports.